WOLFRAM MINERALIZATION IN THE REGIONS OF PRECAMBRIAN-FANEROZOIC TECTONIC-MAGMATIC ACTIVIZATION - IVANOV, V.; KOZAR, M.; GURSKY, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Peculiarities of tectonomagmatic activization displaying and tungsten mineralization associated with that one in the East European, South American, Australian and Indian Platforms are examined. General genetic and mineral types of tungsten ores and certain wellknown deposits, which are localized at named cratons are characterized. Attention to some principal features of ancient tungsten mineralization and prospects of the Ukrainian Shield activized districts to this metal is paid.